1992
DOI: 10.1111/j.1523-536x.1992.tb00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Nausea and Vomiting During Pregnancy: Effects on the Quality of Women's Lives

Abstract: More than 70 percent of all pregnant women experience nausea and vomiting during pregnancy, and 28 percent report that symptoms cause them to change their usual activities. We investigated the magnitude of problems that nausea and vomiting impose on the lifestyle of pregnant women and their families. Twenty-seven women who were experiencing different degrees of nausea and vomiting were selected from 147 pregnant women and asked to participate in semistructured telephone interviews. All participants reported ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
121
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(130 citation statements)
references
References 7 publications
6
121
0
3
Order By: Relevance
“…Of 243 employed women in Vellacott's consecutive series of 500 NVP subjects, 47% felt that job efficiency was impaired and 25% took time off from work. 13 O'Brien et al 14 found that 120 of 147 women (83%) stated that NVP affected their ability to perform usual daily activities. Because these statistics reflect the morbidity of NVP, they are likely to be gross underestimates of the effect that HG has on a pregnant woman's daily life.…”
Section: Introductionmentioning
confidence: 99%
“…Of 243 employed women in Vellacott's consecutive series of 500 NVP subjects, 47% felt that job efficiency was impaired and 25% took time off from work. 13 O'Brien et al 14 found that 120 of 147 women (83%) stated that NVP affected their ability to perform usual daily activities. Because these statistics reflect the morbidity of NVP, they are likely to be gross underestimates of the effect that HG has on a pregnant woman's daily life.…”
Section: Introductionmentioning
confidence: 99%
“…Women in that study also evidenced changes in their behaviors and in the way of dealing with motherhood, appointing differences between pregnancy, when the baby is still being generated, and when, after birth, (s) he is present in their lives; they strongly emphasized bodily transformations though, affirming a negative influence on their sexual life (15) .…”
Section: Discussionmentioning
confidence: 99%
“…A study involving 147 pregnant women appoints that the symptoms deriving from the pregnancy period, associated with the digestive system, such as nausea and vomiting, caused limitations in the women's daily lives, affected comfort and also reflected in family members' lives (15) .…”
Section: Discussionmentioning
confidence: 99%
“…Nausea and vomiting of pregnancy not only affects the physical health of pregnant women, but can also negatively impact their family, social and occupational functioning [13], [14] . Furthermore, the degree of this negative impact seems to be associated with the severity of NVP [10], [15] .Severe and intractable NVP, hyperemesis gravidarum (HG), occurs in approximately 0.5-2% of pregnancies [16] , and studies specific to HG have also detailed the significant physical, psychological, social and economic toll [17], [18] . Health related quality of life measures the burden of illness.…”
Section: Introductionmentioning
confidence: 99%